Combined empowerment, continuous appraisal, psychological and career counseling improve medical cadets' satisfaction and may potentially offset burnout during internship year. An 18-months successful experience in a tertiary medical center - Shoham, Reut; Robinson, Hanni; Yehiel, Noy; Robinzon, Vered; Nir, Yael Frenkel; Segal, Gad (Frontiers in Public Health, 2024)
BackgroundFollowing graduation, Israeli medical cadets complete a 12-months training period in hospitals, having profound influence on their future career. Burnout, sense of personal and professional uncertainty and disorientation are already notable in this group. The aim of the current study was to assess the potential impact of empowerment, psychological and career counseling on the level of satisfaction and burnout of medicine cadets during their internship year in a tertiary medical center.MethodsIn a tertiary hospital's education authority, we offer constructed, personalized psychological and counseling services with continuous process of appraisal. During an 18-month period we followed their monthly feedback relating to satisfaction, learning experience and level of socialization. The study was designed as comparative research assessing cadets' satisfaction before, and after intervention as a surrogate marker for their burnout.ResultsComparison of measured parameters showed statistically significant improvement, with interns stationed in the surgical departments (n = 86) showing the highest degree of improvement: the extent of acquiring new knowledge and competencies (1 to 5 Likert) went from 2.2 ± 1.0 to 3.3 ± 1.42; p < 0.005; experience from the absorption process into the department (LQR from 2.6 ± 1.2 to 3.5 ± 1.56; p < 0.05), degree of motivation to recommend peers to apply for residency (LQR from 2.3 ± 1.0 to 3.1 ± 1.6; p = 0.05) and the experience of being accepted to the department by the staff nurses (LQR from 2.7 ± 1.3 to 3.5 ± 1.1; p < 0.05).ConclusionsA combined, ongoing process of appraisal, empowerment, psychological and career counseling seems promising in the relenting effort to improve cadets' satisfaction and hopefully withhold the burnout process of young physicians.